Jobelyn Attenuates Oxidative Stress and Improves Memory Performance in Mice Exposed to Anoxic Stress - Omorogbe, Osarume (Drug Research, 2019)
Objective Chronic stress impairs memory by damaging brain cells via induction of oxidative stress. Hence, the use of agents with antioxidant activity is being investigated as potential drugs against chronic stress-induced memory decline. This study evaluated the effect of Jobelyn® (JB), a potent antioxidant food supplement on memory deficit induced by anoxic stress in mice and on brain levels of biomarkers of oxidative stress.Method Male mice were distributed into 6 groups (n=6): group 1 (non-stress control) and group 2 (stress control) were a given saline, groups 3–5 received JB (5, 10, 25 and 50 mg/kg) while group 6 had donepezil-DP (1 mg/kg). Thirty minutes later, mice in groups 2–5 were exposed twice to anoxic condition for 15 min in acute anoxic stress. However, in sub-chronic anoxic stress, mice in groups 2–6 were subjected to the same anoxic condition for 15 min twice daily for 5 consecutive days. Thereafter, memory performance was assessed in each case using Y-maze paradigm. The concentrations of biomarkers of oxidative stress (glutathione and malondialdehyde) were only determined in the brains of mice exposed to sub-chronic anoxic stress.Results Mice exposed to sub-chronic anoxic stress had impaired memory function, which was significantly attenuated by JB. The increased oxidative stress as shown by elevated levels of malondialdehyde and decreased concentrations of glutathione was also reduced by JB.Conclusion The results of this study suggest that the antioxidant activity of Jobelyn® might be contributing to its ability to attenuate sub-chronic anoxic stress-induced memory deficits in mice.
Keywords: Jobelyn; anoxic stress; memory impairment; oxidative stress